Hubungan Pendisiplinan Orang Tua dan Masalah Sosial Emosional Anak Usia Sekolah - Betari Neysha Arethusa; Afra Hafny Noer; Lucia Voni Pebriani (Ilmu Psikologi Universitas Yudharta Pasuruan, 2022)
Parents have an important role in the children’s social emotional skill development, one of the ways through discipline. Parents do discipline by responding, correcting children’s behavior, which is considered behavior that does not follow expectations. There are 2 types of discipline, punitive and non-punitive, each of which has a different impact on children’s development. This study aims to determine the relationship between the type of discipline applied by parents to children with problems with social-emotional abilities in school-age children. The researcher used the Dimensions of Discipline Inventory (DDI) and Strength and Difficulties Questionnaire (SDQ). Subjects in this study were 92 parents who have school-age children aged 6-11 years in Bandung. The correlation test results showed that the type of non-punitive discipline with SDQ had no relationship (rs=0,027, p=0,799). Meanwhile, there was a sufficiently positive relationship between the type of punitive discipline and SDQ, it was statistically significant (rs=0,305, p=0,003). These results indicate that there is a relatively positive correlation between the type of punitive discipline and the emergence of children's social-emotional problems. This shows that its important for parents to pay attention to the type of discipline that is applied to their children to prevent social-emotional problems from arising.